PENGARUH CURRENT RATIO, DEBT RATIO, DAN TOTAL ASSET TURNOVER RATIO TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Edi sutanto; Yeti Atun (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2020)
Each company aims to profit and maintain the continuity of the company. When the company is unable to maintain financial performance stability, then the company will experience financial distress financial problems. financial ditress marked by negative operating profit of the company for two consecutive years and this occurred in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2018. This research was conducted with the aim of knowing the influence of current ratio, debt ratio and total asset turnover ratio on financial distress to Manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2017-2018 both partially and simultaneously.The research method used in this study is quantitative research method and descriptive research, the population of this research is all manufaktur companies listed on the Indonesia Stock Exchange (IDX) period 2017-2018 which is as many as 117 companies. Research sample of 59 companies with financial report data 2017-2018 with 181 research data. Sample techniques use purposive sampling. Data analysis techniques use descriptive statistics and logistics regression analysis with processing techniques using SPSS 20. It concluded that the results of the determination coefficient using nagelkerke's R Square amounted to 29.9% and the hypothetical test results of this study were either partially and simultaneously current ratio, debt ratio and total asset turnover ratio influential and significant to financial distress. Advice for the company, by improving the performance of the company to avoid financial distress. For other researchers, it is recommended to add free variables other than current ratio, debt ratio and total asset turnover ratio to things that may affect financial distress.